2016
DOI: 10.1007/s10388-016-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Registry of Esophageal Cancer in Japan, 2009

Abstract: 276 institutions in Japan. Tumor locations were cervical: 4.4 %, upper thoracic: 11.9 %, middle thoracic: 48.0 %, lower thoracic: 27.7 % and EG junction: 6.6 %. Superficial carcinomas (Tis, T1a, T1b) were 36.7 %. As for the histologic type of biopsy specimens, squamous cell carcinoma and adenocarcinoma accounted for 90.5 and 3.8 %, respectively. Regarding clinical results, the 5-year survival rates of patients treated using endoscopic mucosal resection, concurrent chemoradiotherapy, radiotherapy alone, chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…It has been reported that the 5-year survival rate post-esophagectomy was 52% for patients with no residual tumor, but decreased to only 14% if residual tumors were present27. To increase the possibility of complete resection, more than 85% of patients with T2-3N (+) and T4 who underwent surgical resection received (neo-) adjuvant treatment in our hospital.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the 5-year survival rate post-esophagectomy was 52% for patients with no residual tumor, but decreased to only 14% if residual tumors were present27. To increase the possibility of complete resection, more than 85% of patients with T2-3N (+) and T4 who underwent surgical resection received (neo-) adjuvant treatment in our hospital.…”
Section: Discussionmentioning
confidence: 93%
“…Cervical esophageal cancer is relatively uncommon, representing 4.4% of all esophageal cancers . Because the majority of these patients are diagnosed with locally advanced disease, which may invade into adjacent organs, its prognosis is believed to be poor.…”
Section: Introductionmentioning
confidence: 99%
“…According to a national cancer registry in Japan, reconstructions using the jejunum accounted for 5.4% of all esophageal cancer resections [11]. The incidence of incisional hernia after this surgery was unclear.…”
Section: Discussionmentioning
confidence: 99%